PERAN ASEAN CENTRE FOR BIODIVERSITY (ACB) DALAM MELINDUNGI KEANEKARAGAMAN HAYATI DI INDONESIA (STUDI KASUS: TAMAN NASIONAL GUNUNG LEUSER) - Yogi Prambudi; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research aims to explain the role of ASEAN Centre for Biodiversity (ACB) on conserving biodiversity in Indonesia, specifically in Gunung Leuser National Park (GLNP). As an intense conservation area, GLNP represents Indonesia’s biodiversity richness. However, the biodiversity faces biodiversity loss which is mostly caused by human activities: wild forest clearance, illegal logging, poaching and over-harvesting. Conserving the biodiversity is necessary.The method of this research writings is qualitative-descriptive. Research is written through in-depth analysis technique in analyzing the main questios. The method of data collecting is done by collecting primary data: direct observation to GLNP and unstructured-interviews; and secondary data: books, journals, websites and other sourcesACB is an institution as ASEAN response towards biodiversity loss in ASEAN region. Awareness on losing essential life supporter makes ACB concern its works by doing sustainable-conservation: conserving biodiversity, especially degraded ones, and; improving livelihood of local people. Role of ACB on conserving biodiversity in GLNP are partner for Balai Besar Taman Nasional Gunung Leuser (BBTNGL). It is being done through some acts, such as: ACB becoming conservation-consultation forum, ACB becoming facilitator of financial assistance and ACB become an independent secretariat that set qualification for a well-deserved AHP to get a grants. Keywords: ASEAN Centre for Biodiversity (ACB), Biodiversity, Biodiversity Loss, Gunung Leuser National Park (GLNP), Conservation